Crisis mitigation in livestock dependant systems: The role and limitations of current initiatives for livestock systems in South Africa - Lebbie, S.H.B. (Bunda College of Agriculture, 2001)
Livestock are central to the livelihoods of livestock-dependent systems in Africa, particularly pastoralists and agro-pastoralists. Over the years, however, climatic extremes in this sub-region have impacted the agricultural production systems including livestock-dependent systems and hence the livestock owners. In recognition of this problem, the SADC member states have elaborated a Sub-Regional Action Programme (SRAP) to Combat Desertification in Southern Africa under the umbrella of the SADC Environment and Land Management Sector. In addition, the sub-region has, with the assistance of collaborating partners, established early warning systems (EWS) to assist farmers anticipate and prepare for climatic extremes such as drought. This paper discusses these initiatives focusing on their role and limitations to serve the livestock sector and suggests opportunities to enhance their effectiveness to support and improve the management of livestock and drought.